معنى الحياة وعلاقته بالانتكاسة لدى مرضى الإدمان في الأردن - خوالده، أحمد سليمان ظاهر; المهايرة، عبدالله سالم فرحان (الجمعية الأردنية للعلوم التربوية, 2024)
هدفت الدراسة إلى الكشف عن العلاقة بين معنى الحياة والانتكاسة ومستوى كل منهما لدى مرضى الإدمان في الأردن، وقد تم استخدام المنهج الوصفي الارتباطي للتوصل لنتائج الدراسة، وتكونت عينة الدراسة من (385) مريض إدمان من مراجعي المركز الوطني لتأهيل المدمنين ومركز علاج الإدمان التابع لمديرية الأمن العام، ولتحقيق أهداف الدراسة تم تطوير مقياسي معنى الحياة والانتكاسة. وأظهرت نتائج الدراسة أن مستوى كل من معنى الحياة والانتكاسة جاءا بمستوى متوسط، كما وأظهرت النتائج وجود علاقة عكسية بين معنى الحياة والانتكاسة لدى عينة من مرضى الإدمان في الأردن، وأوصت الدراسة بالتركيز على دراسة الأبعاد الروحية في أثناء تناول معنى الحياة لدى مرضى الإدمان والعمل على البرامج التي تحسن مستوى معنى الحياة لدى مرضى الإدمان. The study aimed to reveal the relationship between the meaning of life and relapse among addiction patients in Jordan, and the level of the two variables. The study followed the descriptive correlational methodology. The sample of the study consisted of (385) addiction patients who attended the National Center for Rehabilitation of Addicts and the Addiction Treatment Center of the Public Security Directorate. To achieve the objectives of the study, the meaning of life scale and relapse scale were developed. The results of the study showed that the level of meaning of life and relapse were "medium" and the results showed there was an inverse relationship between the meaning of life and relapse among a sample of addiction patients in Jordan. The study recommended focusing on the study of the spiritual dimension while dealing with the meaning of life for addicted patients, and working on programs that enhance that level of meaning of life for addicted patients.
Keywords: المؤثرات العقلية -- الاضطرابات النفسية -- مدمنو المخدرات -- الأردن